Pengaruh Strategi Konflik Kognitif Terhadap Penguasaan Konsep Pada Materi Fluida Siswa SMAN 3 Mataram Tahun Ajaran 2016/2017 - Raehana Tuqalby; Sutrio Sutrio; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to determine the effect of cognitive conflict strategy on the mastery of the concept of student fluid material SMAN 3 Mataram academic year 2016/2017. This research is a quasi experimental research using untreated control group design with pretest and posttest. The population in this study is all students of class XI IPA SMAN 3 Mataram. Research sampling using cluster random sampling technique, so selected class XI IPA 1 as experiment class that will be given treatment in the form of cognitive conflict strategy and class XI IPA 2 as control class to be given treatment in the form of conventional instruction (direct instruction). Concept master data collection is done by multiple choice test. Hypothesis test using t-pooled variance test. Increased concept mastery is determined based on the results of the N-gain test. The result of the research shows that there is an increase of mastery of student concept in both classes. The experimental class experienced a higher conception mastery than the control class except on the viscosity material. Material of continuity equation in experiment class has the highest increase. This suggests that the cognitive conflict strategy applied successfully increases the mastery of students' concepts in physics learning